Investigating The Presence Of Groundwater At Landslide Affected Areas Using The 2D Geoelectrical Method (Case Study Of Argopuro Mountain Slope At Suci Village, Jember) - Nurul Priyantari; Agus Suprianto; Irdiana Faiqah (Lambung Mangkurat University Press, 2023)
The presence of groundwater and landslides have a close relationship, especially in the context of the influence of groundwater on slope stability. High groundwater levels can cause an increase in hydrostatic pressure on slopes, reduce soil carrying capacity, and reduce friction between soil particles. A decrease in the carrying capacity of the soil causes a decrease in the carrying capacity of the soil on the slopes. This condition can lead to a decrease in slope stability and the potential for landslides to occur. Therefore, it is essential to map subsurface conditions in landslide-affected areas and identify the potential aquifers. One of the geophysical methods that can describe this is the resistivity geoelectric method. The working principle of the resistivity geoelectric method is to inject an electric current into the soil through a pair of current electrodes and then read the electric potential difference through a pair of potential electrodes so that the resistivity value in the medium below the soil surface can be determined. Data collection was carried out in three tracks. The resistivity value on the first track is in the range (4.09 – 0.5) Ωm and reaches a depth of 31.6 m. The resistivity value on the second track is in the range (6.91 – 105) Ωm and reaches a depth of 31.6 m. The resistivity value on the third track is in the range (13.1 – 512) Ωm and reaches a depth of 15.9 m. Finally, there are also indications of the presence of groundwater in the first and second tracks, which are characterized by low resistivity values in the resistivity cross-sectional images